The Integration of Digital Library Services in Blended Learning Environments: A Malaysian Higher Education Perspective - Md Amin, Norasieh (Auckland University of Technology, 2015)
University libraries in Malaysia have increasingly utilized modern computer technology to improve services provision, and the country’s library landscape has been transformed into one that is more digital than physical. Simultaneously, the rapid advancements in information and communication technology (ICT) have seen learning environments in Malaysian universities move into blended learning, a fusion of face-to-face and online learning. One of the aims of the government’s Vision 2020 was to establish the country as a regional centre of excellence in education. Towards forwarding such aims, the Ministry of Higher Education (MOHE) has introduced various initiatives, including a call for an integration or “merger of e-library services, e-learning services and computing services to facilitate collaboration and learning” (MOHE, 2006, p. 116). From my point of view as a librarian, digital library services have extended existing library services and ICT has been extensively incorporated in services provision. However, blended learning has been investigated by the academic community without a focus on the role of libraries, and there is a scarcity of research investigating the intertwining relationship between digital library services and blended learning. The research presented in this thesis aimed to grasp a holistic understanding of the relationship between digital library services and blended learning by exploring librarian, teacher and student perspectives on the integration of digital library services in blended learning environments in Malaysia. The research thus explored 1) librarians’ integration of digital library services in blended learning environments, and 2) teachers and students’ perceptions and experiences of the integration of digital library services in a blended learning environment. I employed a qualitative case study methodology and drew ideas from third-generation activity theory (AT) to construct my theoretical framework. I used interviews and documents as data collection methods and selected a Malaysian university as the bounded case. Twenty-six interviews between 15 and 75 minutes long were conducted with 43 participants. Interview transcripts were transcribed and analysed, and NVivo was used to assist the analysis. This research’s findings include the following: 1) the integration of digital library services in blended learning occurred mainly through ubiquitous accessibility of the digital library, which suit distance learners well. However, the use of the digital library services was influenced by several internal and external factors including language and cultural barriers, access and connectivity, familiarity, preferences and alternatives. 2) Despite issues and challenges, librarians have made continuous efforts to improve library services and in particular their use of Library 2.0 in reaching library users of diverse localities. 3) Access, connectivity, language and cultural barriers have led to tensions that differentiate factors influencing participants in cities and rural areas in using digital library services and these tensions suggested a digital divide. The findings of this research have implications for academic libraries and blended learning in Malaysia.
Keywords: Digital library; Digital library services; Blended learning; Online learning; Self-paced learning; Library 2.0; Digital divide; Blended librarianship